Enteral self-expandable metal stent placement for malignant afferent limb syndrome using single-balloon enteroscope: report of five cases - Yane, Kei; Katanuma, Akio; Hayashi, Tsuyoshi; Takahashi, Kuniyuki; Kin, Toshifumi; Nagai, Kazumasa; Tanaka, Kazunari; Komatsu, Naohiro; Endo, Masato; Kobayashi, Yousuke; Takigawa, Yukiko; Utsunomiya, Ran (Endoscopy International Open, 2018)
Endoscopic enteral self-expandable metal stent (SEMS) placement is a useful alternative treatment option for malignant afferent limb syndrome (ALS). We investigated the safety, efficacy, and follow-up results of enteral SEMS placement using a single-balloon enteroscope for the treatment of malignant ALS.